Analysis of morphometric maps of the oil Valley Basin and its role in the development of agricultural lands using GIS Geographic Information Systems - Dr. Ismail Fadel Khamis Mustafa al Bayati (Journal of College of Education, 2024)
The analysis of the morphometric characteristics of the oil Valley Basin and its role in the development of rural agriculture using Geographic Information Systems (GIS) includes the study of geographical and cadastral features of the area and the use of geological and geomorphological data to understand the territory and identify its potential uses. Geographic Information Systems (GIS) have a role in the analysis of spatial and geographical data and provide important insights for the development of rural agriculture. In the context of the oil Valley Basin, important morphometric characteristics can include: Elevation and slope: the analysis of slopes and elevations can help determine the best areas for a particular agriculture based on the slope of the land and water drainage. The topography and understanding of the geological structure of the area can reveal groundwater resources and guide the use of land for specific agricultural purposes. The use of GIS techniques to monitor changes in the terrain over time can help determine the sustainability of Agriculture and counteract erosion and desertification phenomena. Determining the quality and characteristics of the soil can contribute to making informed decisions about the types of plants grown and the best agricultural practices. The integration of this information into the GIS system can help to make better decisions on agricultural planning and land management, identify the most suitable planting sites and direct efforts to increase agricultural productivity in the oil Valley. Using geographical data and their analysis by GIS, it is possible to identify the needs, opportunities and challenges of rural agriculture in this region and develop strategies to promote its development sustainably and effectively.
Keywords: Spatial analysis, GIS, water basins, modeling, development, countryside , Oil Valley